Eksistensi Jurnal Ilmiah di Universitas Islam Negeri Alauddin Makassar (Perannya Dalam Mendukung Universitas Islam Negeri Alauddin Makassar Menuju World-Class University) - Hildawati Almah (Program Studi Ilmu Perpustakaan UIN Alauddin, 2015)
One of mediums that a researcher might use to publish his or her papers is through scientific journals. Different with others information tools such as book, scientific journal is a serial publishing in which it is always published periodically and determined by its publishers. All articles within a journal usually should be peer-reviewed before they were published. It made journals containing such quality works compared with other works. The current study is aimed to survey UIN Alauddin lecturers’ perception on UIN Alauddin’s electronic journals. The number of research sample was 54 participants vary from all departments in its campus. The survey found that there were as many as 31 scientific journals being published throughout the site (even though some still remained empty with an article). Meanwhile, based on the participants survey, the existence of its electronic journals has good responses. In terms of its views, organizing, and socialization needed to be enhanced.